2005
DOI: 10.1002/cphc.200400510
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Dependent Photoacidity State of Pyranine Monitored by Transient Mid‐Infrared Spectroscopy

Abstract: We investigate with femtosecond mid‐infrared spectroscopy the vibrational‐mode characteristics of the electronic states involved in the excited‐state dynamics of pyranine (HPTS) that ultimately lead to efficient proton (deuteron) transfer in H2O (D2O). We also study the methoxy derivative of pyranine (MPTS), which is similar in electronic structure but does not have the photoacidity property. We compare the observed vibrational band patterns of MPTS and HPTS after electronic excitation in the solvents: deutera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
181
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(189 citation statements)
references
References 68 publications
8
181
0
Order By: Relevance
“…The results presented here are in contrast to visiblepump IR-probe studies, which do not observe the fast component of the deprotonation kinetics and only see the slower ∼90 ps decay. 9 Because the experiments and analysis given above unambiguously separate the time dependence of the Stokes shift from the deprotonation dynamics, it is clear that the ∼3 ps component of the spectral dynamics is not part of the Stokes shift (∼1 ps) and that the deprotonation is biexponential on times short (hundreds of picoseconds) compared with diffusive contributions. …”
Section: Discussionmentioning
confidence: 94%
“…The results presented here are in contrast to visiblepump IR-probe studies, which do not observe the fast component of the deprotonation kinetics and only see the slower ∼90 ps decay. 9 Because the experiments and analysis given above unambiguously separate the time dependence of the Stokes shift from the deprotonation dynamics, it is clear that the ∼3 ps component of the spectral dynamics is not part of the Stokes shift (∼1 ps) and that the deprotonation is biexponential on times short (hundreds of picoseconds) compared with diffusive contributions. …”
Section: Discussionmentioning
confidence: 94%
“…With increasing delay, these absorption bands decay and a new absorption at 1503 cm −1 grows in that is assigned to the conjugated photobase PTS * − . [14][15][16][17][18][19][20][21] Therefore, the decay and rise of these bands reflect the release of the proton by HPTS * . [14][15][16][17][18][19][20][21] The transient spectra in the frequency region between 1600 and 2100 cm −1 are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…13 Recently, the proton transfer between HPTS and different carboxylate bases dissolved in water has been studied by probing the vibrations of the photoacid and an accepting base with femtosecond midinfrared laser pulses. [14][15][16][17][18][19][20][21] These studies showed that the SCK model does not provide an adequate description of the data at all delay times. It was also found that there is not a single well-defined reaction distance at which proton transfer takes place.…”
Section: -3mentioning
confidence: 99%
See 2 more Smart Citations